Effect of treating tall fescue pasture with Mefluidide on performance of grazing steers - Joseph L. Moyer; Lyle W. Lomas (Kansas Agricultural Experiment Station Research Reports, 1985)
Mefluidide (Embark® ) delays maturity and suppresses seed head formation in grasses. Mefluidide treatment increased the crude protein content of fescue pasture and improved daily gain of grazing steers by 14.3% (.21 lb per head daily).
Keywords: Cattlemen' s Day; 1985; Kansas Agricultural Experiment Station contribution; no. 85-319-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 470; Beef; Fescue; Mefluidide; Performance; Steers